E-Book Ipa Terintegrasi Potensi Lokal Pembuatan Petis Berbasis PBL-ESDUntuk Meningkatkan Kemampuan Literasi Sains Siswa Smp - Kamila; Sabar Nurohman; Ismail Fikri (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to determine the effect of science e-books integrated with local potential based on PBL-ESD on students' science literacy skills on the sub-topic of mixture separation methods. This research is an experimental research with One Group Pretest-Postest research design. The population in this study were VIII grade students of SMP Negeri 8 Yogyakarta and the sample technique used was random sampling, namely VIII-f and VIII-i classes totaling 55 students. The instrument used was a test in the form of multiple choice questions to measure students' science literacy skills. Paired Samples T-Test test results obtained Sig. (2-tailed) of 0.00 <0.05 which shows there is a change in the improvement of students' science literacy skills between before and after using the e-book. The increase in students' science literacy skills is supported by the N-gain value of 0.24 which is included in the low category and the effect size test results of 0.59 which shows a moderate category. The highest indicator of students' science literacy ability is explaining phenomena scientifically . So it can be concluded that there is an effect of science e-book integrated with local potential based on PBL-ESD on students' science literacy skills on mixture separation material.